The Construction of Religious Identity of Young Muslim Women in Tabeak Blau II Village in The Context of Islamic Education - Zepi Sartika; Surohim; Lety Febriana (MADINAH, 2025)
This research aims to describe the process of constructing religious identity among young Muslim women in Tabeak Blau II Village, Lebong Regency, Bengkulu Province, and identify factors within the context of Islamic education that influence it, using Berger and Luckmann's social construction theory. The method employed is descriptive qualitative, involving observation, semi-structured interviews with 15 primary informants and supporting informants, and documentation. Data analysis was conducted using the Miles and Huberman model. Findings indicate that religious identity construction occurs through three stages: externalization (expression through basic worship and Islamic symbols, but influenced by social media trends), objectivation (Islamic values as social norms from family, school, and community), and internalization (instilling values into oneself, though still low in social aspects). Key influencing factors include Islamic education in the family (mothers as role models), schools (PAI teachers as exemplars), community (low participation in religious activities), and social media (dominance of symbolic content). The novelty of this research lies in exploring the rarely studied rural context, particularly the fusion of local traditions with digital culture. Theoretically, it enriches Islamic education studies through a social construction perspective in the digital era, while practically, it provides reflection material for young Muslims to internalize authentic values, references for educators in designing identity-strengthening programs, and a foundation for future researchers to expand studies on women's religious identity in rural areas